Extraction of K+, Ca2+, Mg2+, Na+ in saline soil by mono or multi-germ sugar beet - Valdivia, Sergio; Pinna, Jorge; Valdivia Salazar, Sergio (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2025)
Approximately 33 % of surface of irrigated valleys in Peruvian northern coast, has a bad drainage or salinity problem. Sugar beet has good yields in those soils (90 t.ha-1).  The objective of present work was to know if in those soils there is a relationship between soil K, Ca, Mg, Na, and its extraction by sugar beet, and if they contribute with crop salinity tolerance. Experiment was made in Chicama valley, with randomized complete block design, ten treatments: five multi-germ cultivars, five monogerm; six replications. In each plot five soil sub-samples were taken, mixed in the field making one sample per plot, and available K, Ca, Mg, Na analyzed. Sugar beet extractions of those elements were evaluated in buried dry bio mass (roots) and aerial (leaves + crowns). Sugar beet mono or multi-germ did not absorb more K, Ca, Mg, Na if their quantity augmented in soil; for that is not an efficient soil “reclamator”. K and Na contributed to sugar beet salt tolerance, Ca could give salt tolerance, Mg had any action in salt tolerance. In those soils where there are large amounts of CaCO3, Ca was absorbed with low or high available Ca soil amounts.  Na contributed to salt tolerance because it was “included”. Mono or multi-germ showed no differences “including” nutrients.